IMPLEMENTATION OF REGIONAL REGULATION OF NORTH SUMATRA PROVINCE NUMBER 1 OF 2019 CONCERNING FACILITATION OF PREVENTION OF ABUSE OF NARCOTICS, PSYCHOTROPICS, AND OTHER ADDICTIVE SUBSTANCES FROM THE PERSPECTIVE OF SIYASAH DUSTURIYAH - Harahap, Surtan Gusnaldi; Ramadhan, Muhammad (Journal Analytica Islamica, 2025)
This study aims to analyze the implementation of North Sumatra Provincial Regulation Number 1 of 2019 concerning the Facilitation of the Prevention of Abuse of Narcotics, Psychotropics, and Other Addictive Substances (NAPZA) from a siyasah dusturiyah perspective. Using a qualitative approach with a combination of normative and empirical juridical, data were obtained through interviews, observations, and a review of legal documents and Islamic literature. The results show that this regulation has substantially emphasized the aspects of prevention, rehabilitation, and empowerment in line with the principles of maqashid al-syari'ah, especially the protection of the mind (hifz al-'aql) and soul (hifz al-nafs). However, the effectiveness of implementation is still low due to budget constraints, minimal rehabilitation facilities, weak coordination between agencies, and low community participation. From a siyasah dusturiyah perspective, this regulation already reflects the state's efforts to realize the public welfare, but has not been optimal in practice. This research emphasizes the need for integrative strategies based on Islamic values, such as collaboration with religious scholars, optimizing zakat funds for rehabilitation, and a humanistic approach to da'wah. Thus, this research contributes to strengthening Sharia-based public policies and offers a more effective and transformative model for implementing regional regulations.